Dysregulated inflammasome activity in intestinal inflammation – Insights from patients with very early onset IBD - Illig, David; Kotlarz, Daniel (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD) is a multifactorial disorder triggered by imbalances of the microbiome and immune dysregulations in genetically susceptible individuals. Several mouse and human studies have demonstrated that multimeric inflammasomes are critical regulators of host defense and gut homeostasis by modulating immune responses to pathogen- or damage-associated molecular patterns. In the context of IBD, excessive production of pro-inflammatory Interleukin-1β has been detected in patient-derived intestinal tissues and correlated with the disease severity or failure to respond to anti-tumor necrosis factor therapy. Correspondingly, genome-wide association studies have suggested that single nucleotide polymorphisms in inflammasome components might be associated with risk of IBD development. The relevance of inflammasomes in controlling human intestinal homeostasis has been further exemplified by the discovery of very early onset IBD (VEO-IBD) patients with monogenic defects affecting different molecules in the complex regulatory network of inflammasome activity. This review provides an overview of known causative monogenic entities of VEO-IBD associated with altered inflammasome activity. A better understanding of the molecular mechanisms controlling inflammasomes in monogenic VEO-IBD may open novel therapeutic avenues for rare and common inflammatory diseases.